2006
DOI: 10.1287/mksc.1050.0182
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Group Interactions on Satisfaction Judgments: Satisfaction Escalation

Abstract: This study investigates how people's satisfaction judgments are modified after they interact with other group members. It integrates research on customer satisfaction and social influence to develop hypotheses about how an individual's satisfaction is influenced by discrepancies between her expectations about the satisfaction of other group members and their actual opinions as revealed in group discussion. It also considers how this effect is moderated by the individual's susceptibility to social influence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…This moderating effect of interactions on user satisfaction mostly comes from the individual's susceptibility to social influence and perceptions of group cohesiveness [28]. Recent empirical study results repeatedly confirm that good virtual interactions can lead to consumer website satisfaction, and undesirable interactions will negatively affect service quality and user satisfaction [69,89,97].…”
Section: E-auction Web Interactivitymentioning
confidence: 99%
“…This moderating effect of interactions on user satisfaction mostly comes from the individual's susceptibility to social influence and perceptions of group cohesiveness [28]. Recent empirical study results repeatedly confirm that good virtual interactions can lead to consumer website satisfaction, and undesirable interactions will negatively affect service quality and user satisfaction [69,89,97].…”
Section: E-auction Web Interactivitymentioning
confidence: 99%
“…Perception can influence the strength of subsequent judgements on that attribute. By the same token, it can be said that the perception of knowledge transfer effectiveness may be directly influenced by initial expectations (Bohlmann et al 2006). If a particular actor believes that the process is effective, effectiveness can be taken-for-granted as an external belief that will influence future behaviours.…”
Section: Performance and Effectiveness Of Knowledge Transfer: An Openmentioning
confidence: 99%
“…On the basis of experimental data, Rao and Steckel (1991) verified that a decision model that incorporates the polarization effect outperforms models that do not. Recently, Bohlmann, Rosa, Bolton, and Qualls (2006) demonstrated that satisfaction judgments of both individual consumers and organizational buyers are susceptible to the polarizing influence of group interactions-a phenomenon they labeled as "escalation. "…”
Section: Attitude Polarization Among Consumersmentioning
confidence: 99%
“…The aggravating effect of NWOM A large amount of WOM occurs in the context of group discussions with family and friends (Ward & Reingen, 1990), colleagues (Bohlmann et al, 2006), and strangers (Schlosser, 2005). When dissatisfied consumers exchange NWOM information in a group setting, dissatisfaction should be escalated.…”
Section: Attitude Polarization Among Consumersmentioning
confidence: 99%
See 1 more Smart Citation